Preparation method of microcrystalline glass, chemically strengthened microcrystalline glass and microcrystalline glass product
By preparing microcrystalline glass with specific crystal ratios and performing chemical strengthening treatment, the shortcomings of existing microcrystalline glass products in terms of optical and mechanical properties are solved, and the combination of high mechanical strength and excellent optical properties is achieved, which is suitable for a variety of electronics and optical equipment.
Patent Information
- Application Number
- CN202411174038.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-17
AI Technical Summary
Existing microcrystalline glass products are difficult to meet the wide range of application requirements in terms of optical performance and mechanical strength performance, especially in the fields of excellent performance requirements in consumer and commercial electronic equipment, optical components and photovoltaic devices.
By preparing a microcrystalline glass containing lithosparia, lithium silicate and lithium disilicate, combined with specific crystallographic ratios and heat treatment processes, a microcrystalline glass with a crystallinity of less than or equal to 90% is prepared, and chemically Strengthening treatment improves its surface compression stress and four-point bending strength.
It achieves the balance between mechanical strength and optical properties of microcrystalline glass products, has high Vickers hardness, low haze and high transmittance, and is suitable for a variety of application scenarios.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of material technology, and in particular to the field of glass technology. Specifically, the present application discloses a method for preparing microcrystalline glass, chemically strengthened microcrystalline glass, and microcrystalline glass products. Background Art
[0002] Glass-ceramic products such as glass cover plates, back plates, housings, and the like are widely used in consumer and commercial electronic devices, such as smart phones, tablet computers, etc. Of course, in the known material classification, glass-ceramic products can also be widely used in various other scenarios, such as stoves, cooking utensils, tableware, optical components, photovoltaic devices, etc. At present, many application fields require glass-ceramic to provide excellent optical properties and high mechanical strength properties, but the glass-ceramic provided in the relevant technology is still difficult to meet the actual application requirements.
[0003] It is worth noting that the techniques described in this section are not necessarily techniques that have been previously conceived or employed. Unless otherwise indicated, it should not be assumed that any technique described in this section is considered to be prior art simply because it is included in this section. Similarly, unless otherwise indicated, the issues mentioned in this section should not be considered to have been recognized in any prior art. Summary of the invention
[0004] The present application provides a method for preparing microcrystalline glass, chemically strengthened microcrystalline glass and microcrystalline glass products, aiming to solve one of the problems in the related art at least to a certain extent.
[0005] In a first aspect, the present application provides a microcrystalline glass, the crystalline phase of which includes petalite, lithium disilicate and lithium silicate, and the degree of crystallinity is less than or equal to 90%; the ratio of the content of petalite to the total crystal content is 45-60%, the ratio of the content of lithium disilicate to the total crystal content is 30-45%, the ratio of the content of lithium silicate to the total crystal content is less than or equal to 13%, and the ratio of the total content of petalite and lithium disilicate to the total crystal content is greater than or equal to 75%.
[0006] Optionally, the crystal phase of the glass-ceramics further includes at least one of lithium phosphate and β-spodumene.
[0007] Optionally, the crystallinity of the glass-ceramics is 80-85%.
[0008] Optionally, the content of petalite accounts for 50-55% of the total crystal content, and / or the content of lithium disilicate accounts for 35-40% of the total crystal content, and / or the content of lithium silicate accounts for 8-13% of the total crystal content.
[0009] Optionally, the components of the microcrystalline glass include, by weight percentage: SiO2: 70-75%, B2O3: 0.35-1.2%, Al2O3: 7.5-9.5%, Na2O: 0.5-1.5%, Li2O: 9.5-12%, P2O5: 1.8-2.6%, and ZrO2: 3.5-5.5%.
[0010] Optionally, the components of the microcrystalline glass include, by weight percentage: SiO2: 70-72%, B2O3: 0.5-1.2%, Al2O3: 8-9.5%, Na2O: 1-1.5%, Li2O: 10.5-12%, P2O5: 1.8-2.6%, and ZrO2: 3.5-5.5%.
[0011] Optionally, the components of the microcrystalline glass, in terms of weight percentage, meet the following conditions: Li2O / (SiO2+Al2O3): 0.1 to 0.2.
[0012] Optionally, the components of the microcrystalline glass, measured in weight percentage, further include: K2O: 0-1%, Y2O3: 0-0.5%, and clarifier: 0-0.4%.
[0013] Optionally, the components of the microcrystalline glass, measured in weight percentage, further include: K2O: 0.5-1%, Y2O3: 0.2-0.5%, and clarifier: 0.2-0.4%.
[0014] Optionally, the microcrystalline glass meets at least one of the following indicators: Vickers hardness greater than or equal to 730 kgf / mm 2 , the average crystal particle size is less than or equal to 30nm, the average transmittance of visible light with a wavelength of 380-780nm is greater than or equal to 85% when the thickness is 0.6mm, the |B| value is less than or equal to 0.6 when the thickness is 0.6mm, and the haze is less than or equal to 0.15 when the thickness is 0.6mm.
[0015] The second aspect of the present application provides a chemically strengthened microcrystalline glass, which is obtained by chemically strengthening the microcrystalline glass described in the first aspect of the present application, and the surface compressive stress of the chemically strengthened microcrystalline glass is greater than or equal to 200MPa, the depth of the compressive stress layer is greater than or equal to 90μm, and the four-point bending strength is greater than or equal to 950MPa.
[0016] The third aspect of the present application provides a method for preparing a microcrystalline glass product, comprising: preparing raw materials of corresponding formula proportions according to the components of the microcrystalline glass; after mixing the raw materials evenly, smelting them at a preset melting temperature for a preset time to obtain a precursor glass; first heat treating the precursor glass at 500-530°C for 0.5-5h, then heat treating it at 550-580°C for 1-4h, and then heat treating it at 680-750°C for 0.5-1.5h, and finally cooling it to room temperature to obtain the microcrystalline glass; wherein the crystalline phase of the microcrystalline glass includes petalite, lithium disilicate and lithium silicate, and the crystallinity is less than or equal to 90%; the ratio of the content of petalite to the total crystal content is 45-60%, the ratio of the content of lithium disilicate to the total crystal content is 30-45%, the ratio of the content of lithium silicate to the total crystal content is less than or equal to 13%, and the ratio of the total content of petalite and the lithium disilicate to the total crystal content is greater than or equal to 75%.
[0017] Optionally, the method for preparing the microcrystalline glass product also includes: after preheating the microcrystalline glass, placing it in a chemically strengthened salt bath for ion exchange treatment; taking out the microcrystalline glass that has undergone the ion exchange treatment from the chemically strengthened salt bath and performing a slow cooling and cleaning treatment to obtain a chemically strengthened microcrystalline glass; wherein the surface compressive stress of the chemically strengthened microcrystalline glass is greater than or equal to 200MPa, the depth of the compressive stress layer is greater than or equal to 90μm, and the four-point bending strength is greater than or equal to 950MPa.
[0018] Optionally, the chemical strengthening salt bath comprises 75% KNO3 and 25% NaNO3 by weight, and the temperature of the ion exchange treatment is 460°C and the duration is 400-500 min.
[0019] As can be seen from the above, according to the preparation method of the microcrystalline glass, chemically strengthened microcrystalline glass and microcrystalline glass products provided by the present application, the crystal phase of the microcrystalline glass includes petalite, lithium disilicate and lithium silicate, and the crystallinity is less than or equal to 90%; the ratio of the content of petalite to the total crystal content is 45-60%, the ratio of the content of lithium disilicate to the total crystal content is 30-45%, the ratio of the content of lithium silicate to the total crystal content is less than or equal to 13%, and the ratio of the total content of petalite and lithium disilicate to the total crystal content is greater than or equal to 75%. Through the implementation of this application, the content and crystal size of different crystal phases are controlled in a specific ratio, which can ensure that the microcrystalline glass products have excellent optical properties while having good mechanical strength properties.
[0020] It should be understood that the content described in this section is not intended to identify the key or important features of the present application, nor is it intended to limit the scope of the present application. The further effects of the above non-conventional optional methods will be described below in conjunction with specific implementations. DETAILED DESCRIPTION
[0021] In order to make the invention purpose, features, and advantages of the present application more obvious and easy to understand, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0022] In the description of the embodiments of the present application, the term "plurality" means two or more than two, unless otherwise clearly and specifically defined; the term "comprising" indicates the presence of the described features, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections; the term "and / or" describes the association relationship of the associated objects, indicating that three relationships may exist. For example, A and / or B may include the three situations of A existing alone, A and B existing at the same time, and B existing alone. The character " / " generally indicates that the associated objects before and after are in an "or" relationship; the term "approximately" means that the content, size, parameter, etc. are not and do not need to be precise. If necessary, they can be approximate or higher or lower. Generally speaking, regardless of whether there is an explicit description, the content, size, parameter, etc. should be "approximately" or "approximately"; the terms "preferably" and "optional" are not used to limit the scope of the present application, nor do they mean that certain technical features are critical or indispensable to the implementation methods of the present application, but should be understood as only indicating specific aspects of the embodiments of the present application.
[0023] Unless otherwise specified in specific circumstances, the numerical ranges recorded in the examples of the present application are intended to include the endpoints of the numerical range and all integers and fractions within the range. When describing a certain amount, solubility or other parameter in the form of a preferred range or a preferred value, it should be understood that it is equivalent to revealing any range by combining any preferred range with a preferred range, a preferred value with a preferred value, or a preferred range with a preferred value, without considering whether this combination is specifically explained in the examples.
[0024] Unless otherwise specified in specific circumstances, the content of components recorded in the examples of the present application is expressed in weight percentage (wt%).
[0025] In order to at least to some extent solve the problem that the optical properties and mechanical strength properties of the microcrystalline glass products provided in the related art are relatively limited, an embodiment of the present application provides a microcrystalline glass, which is a solid material including a crystal phase and a residual glass phase, wherein the crystal phase includes petalite (LiAlSi4O 10), lithium disilicate (Li2Si2O5) and lithium silicate (Li2SiO3), the crystallinity is less than or equal to 90%; the ratio of the content of petalite to the total crystal content is 45-60%, for example, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%; the ratio of the content of lithium disilicate to the total crystal content is 30-45%, for example, 30%, 3 1%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%; the ratio of the content of lithium silicate to the total crystal content is less than or equal to 13%, for example, 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%; the ratio of the total content of petalite and lithium disilicate to the total crystal content is greater than or equal to 75%.
[0026] In practical applications, firstly, the corresponding glass raw materials are weighed and mixed evenly according to the formula of microcrystalline glass, and then melted. The preferred melting temperature in this embodiment is 1580°C. Then, clarification, homogenization, molding, and annealing are performed to obtain a precursor glass, and then the precursor glass is subjected to nucleation and crystallization treatments in sequence to obtain microcrystalline glass. After the nucleation treatment, the glass can grow a crystal nucleus, and after the crystallization treatment, a specific crystal can be grown on the basis of the crystal nucleus. With regard to the crystallization treatment conditions of this embodiment, in an optional implementation manner, the nucleation treatment temperature is 550-580°C, the nucleation treatment time is 2-5h, the crystallization treatment temperature is 680-750°C, and the crystallization treatment time is 0.5-1.5h; in another optional implementation manner, the precursor glass is crystallized using a three-stage heat treatment method, the first step of the heat treatment is a microphase separation treatment, the second step of the heat treatment is a nucleation treatment, and the third step of the heat treatment is a crystallization treatment, wherein the first step of the heat treatment has a temperature of 500-530°C and a time of 0.5-5h, the second step of the heat treatment has a temperature of 550-580°C and a time of 1-4h, and the third step of the heat treatment has a temperature of 680-750°C and a time of 0.5-1.5h.
[0027] In an optional implementation manner of this embodiment, the crystal phase of the microcrystalline glass further includes at least one of lithium phosphate and β-spodumene.
[0028] That is, the main crystalline phase of the crystallized glass-ceramics in this embodiment includes petalite, lithium disilicate and lithium silicate, and the secondary crystalline phase may include at least one of lithium phosphate and β-spodumene.
[0029] In an optional implementation of this embodiment, the content of petalite accounts for 50-55% of the total crystal content, and / or the content of lithium disilicate accounts for 35-40% of the total crystal content, and / or the content of lithium silicate accounts for 8-13% of the total crystal content.
[0030] It is worth mentioning that the embodiment of the present application optimizes the formula of microcrystalline glass. In the optional implementation mode of this embodiment, the components of the microcrystalline glass are measured in weight percentage (wt%), including: SiO2: 70~75%, B2O3: 0.35~1.2%, Al2O3: 7.5~9.5%, Na2O: 0.5~1.5%, Li2O: 9.5~12%, P2O5: 1.8~2.6%, and ZrO2: 3.5~5.5%.
[0031] SiO2 is the basic component of the glass composition provided in the present application, and is a network structure former of glass and glass-ceramics, and forms lithium silicate and lithium disilicate after crystallization. It should be noted that if the content of SiO2 is low, then the crystals formed in the glass-ceramics will become less and the crystals will become coarser, affecting the haze, drop ball test height and other properties of the glass-ceramics and glass-ceramics products. Therefore, the lower limit of the SiO2 content is set to 70%; in addition, if the SiO2 content is higher than a certain level, the glass melting temperature will be high, the material will be difficult to form, and it will not be easy to form, affecting the consistency of the glass. Therefore, the upper limit of the SiO2 content is set to 75%. In some embodiments, the glass composition may contain about 70%, 71%, 72%, 73%, 74%, and 75% SiO2. Preferably, the content of SiO2 is 70 to 72%.
[0032] B2O3 is the basic component of the glass composition provided in the present application, which can reduce the melting temperature of the glass, and at the same time remain in the glass phase after crystallization, ensuring the structural stability of the glass phase and improving the chemical stability of the microcrystalline glass, but too high B2O3 will increase the volatilization during the glass melting process and increase the difficulty of glass homogenization. Based on this, the lower limit of the B2O3 content is set to 0.35% and the upper limit is set to 1.2%. In some embodiments, the glass composition may contain about 0.35%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2% B2O3. Preferably, the content of B2O3 is 0.5-1.2%.
[0033] Al2O3 can be a component that forms a glass network structure, or it can be a cationic network exosome that balances charge. In the present application, all Al2O3 enters the glass network structure, increases the depth of the ion exchange layer and the surface compressive stress of the microcrystalline glass product, improves the chemical stability of the glass and improves the mechanical properties of the glass. On the one hand, if its content is lower than a certain level, it will lead to poor results. Therefore, the lower limit of the mass percentage content of Al2O3 is 7.5%; on the other hand, if the content of Al2O3 is higher than a certain level, the melting and devitrification resistance of the glass will be reduced, and the crystals will easily increase during crystallization, reducing the strength of the microcrystalline glass and microcrystalline glass products. Therefore, the upper limit of the Al2O3 content is 9.5%. In some embodiments, the glass composition may contain about 7.5%, 8%, 8.5%, 9%, and 9.5% Al2O3. Preferably, the content of Al2O3 is 8 to 9.5%.
[0034] Li2O is an essential component that becomes a crystalline phase after crystallization, helps to form lithium-containing crystalline phases such as lithium disilicate, petalite, and lithium silicate, and is also an essential component for chemical strengthening treatment. However, if its content is lower than a certain level, the effect is not good. Therefore, the lower limit of the Li2O content is 9.5%. On the other hand, if too much Li2O is contained, it is easy to reduce the chemical stability of the glass and increase the production cost. Therefore, the upper limit of the Li2O content is preferably 12%. In some embodiments, the glass composition may contain about 9.5%, 10%, 10.5%, 11%, 11.5%, and 12% Li2O. Preferably, the content of Li2O is 10.5-12%.
[0035] Na2O helps to lower the glass transition temperature, crystallization temperature and inhibit the precipitation of unexpected impurities. It exists as other alkali metal oxides besides Li2O, and its lower limit is set to 0.5%. If the introduced Na2O content is too high, the thermal expansion coefficient of the glass will increase and the thermal stability of the glass will be reduced, so the upper limit of its content is set to 1.5%. In some embodiments, the glass composition may include about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% Na2O. Preferably, the content of Na2O is 1 to 1.5%.
[0036] P2O5 helps to improve the low-temperature melting property of glass, can phase separate in the glass to form crystal nuclei, and improve the thermal expansion stability of the glass during the crystallization process. The lower limit of the P2O5 weight percentage content is preferably 1.8%; but if too much P2O5 is contained, it is easy to reduce the devitrification resistance of the glass and produce phase separation of the glass, and the mechanical properties of the glass tend to deteriorate. Therefore, the upper limit of the P2O5 content is 2.6%; in some embodiments, the glass composition may contain approximately 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, and 2.6% P2O5.
[0037] ZrO2 exists as a nucleating agent and helps to improve the chemical stability of the glass. The lower limit of the ZrO2 content in the present application is 3.5%, but if too much ZrO2 is contained, the devitrification resistance of the glass is easily reduced, and the difficulty of controlling the glass crystallization process increases. Therefore, the upper limit of the ZrO2 content is 5.5%. In some embodiments, the glass composition may contain about 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5% ZrO2. It is worth mentioning that since TiO2 will cause the transmittance of the glass to be reduced relative to visible light in a specific wavelength range, it is further preferred that TiO2 is not included in the nucleating agent of this embodiment.
[0038] In this embodiment, 0-1% K2O by mass is optionally introduced into the glass composition, for example, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% K2O. When there are multiple alkali metal oxides in the glass composition, the mixed alkali effect can be exerted in the chemical strengthening process of the microcrystalline glass, and the migration of alkali metal ions can be restricted during the ion diffusion process, which helps to improve the chemical stability of the glass. In addition, the interaction of multiple alkali metal oxides can improve the low-temperature melting and formability of the glass, and has a certain effect on reducing the softening point temperature and molding temperature of the glass, that is, reducing the difficulty of chemical strengthening of the microcrystalline glass. Preferably, the content of K2O is 0.5-1%.
[0039] In this embodiment, Y2O3 with a mass percentage of 0-0.5% is optionally introduced into the glass composition, such as 0%, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5%. The appropriate amount of Y2O3 can improve the density of the glass phase and the overall strength of the microcrystalline glass. If the content of Y2O3 is too high, it will be difficult to obtain a large compressive stress value during the chemical strengthening treatment of the microcrystalline glass. Preferably, the content of Y2O3 is 0.2-0.5%.
[0040] The glass composition of this embodiment may also include a clarifier, which includes one or more components of SnO2 and CeO2, and the mass percentage of the clarifier has a lower limit of 0% and an upper limit of 0.4%. In some embodiments, the glass composition may include about 0%, 0.1%, 0.2%, 0.3%, and 0.4% of the clarifier. Preferably, the clarifier includes SnO2 and CeO2 with a total content of 0.2-0.4%, thereby achieving a composite clarification effect, so that the glass bubbles are removed more thoroughly.
[0041] In an optional implementation manner of this embodiment, Li2O / (SiO2+Al2O3): 0.1-0.2. The ratio of the total content of Li2O to SiO2 and Al2O3 in the glass composition of this embodiment can be 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%. It should be noted that the special design based on the proportional relationship of the component contents effectively generates the expected lithium silicate, lithium disilicate, and petalite crystal phases in the microcrystalline glass, while also ensuring that the actual ratio of the various crystal phases in the microcrystalline glass meets the expected ratio.
[0042] In an optional implementation manner of this embodiment, the components of the microcrystalline glass, measured in weight percentage, also include: Bi2O3: 0-3%.
[0043] In the related art, glass raw materials are melted to obtain precursor microcrystalline glass, and the glass melting temperature in the related art is usually high (generally higher than 1600°C), which makes glass melting difficult. Based on this, this embodiment introduces Bi2O3 components into the glass composition. Bi2O3 can reduce the viscosity of the glass. Since the glass melting temperature is the temperature when log(P)=2, P represents the viscosity of the glass, and thus reducing the viscosity of the glass can reduce the temperature required for glass melting, thereby reducing the difficulty of glass melting. It is worth mentioning that too high a content of Bi2O3 will cause the glass to be colored, so the upper limit of the content of Bi2O3 is set to 3%. In some embodiments, the glass composition may contain about 0%, 0.5%, 1%, 1.5%, 2.0%, 2.5%, and 3% Bi2O3. Preferably, the content of Bi2O3 is 0.8-2.3%.
[0044] In the optional implementation of this embodiment, the crystallinity of the microcrystalline glass is 80-85%. It is worth mentioning that based on the optimized glass formula system and oxide content provided in the embodiment of the present application, combined with the setting of the crystallization process, a higher crystallinity is achieved directly through a single crystallization process, without the need for a composite processing method of pre-crystallization and post-heat treatment to achieve the expected crystallinity, which simplifies the process flow while meeting the expected optical performance and mechanical strength performance.
[0045] It is also worth mentioning that the microcrystalline glass in the embodiment of the present application meets at least one of the following indicators: Vickers hardness is greater than or equal to 730kgf / mm 2 , the average crystal particle size is less than or equal to 30nm, the average transmittance of visible light with a wavelength of 380-780nm is greater than or equal to 85% when the thickness is 0.6mm, the |B| value is less than or equal to 0.6 when the thickness is 0.6mm, and the haze is less than or equal to 0.15 when the thickness is 0.6mm. Preferably, the |B| value is 0.4-0.6 when the thickness is 0.6mm, and the haze is 0.1-0.15%. It can be seen that the microcrystalline glass of the embodiment of the present application can achieve a good balance between optical performance and mechanical strength performance.
[0046] Next, an embodiment of the present application also provides a chemically strengthened glass-ceramic, which is obtained by chemically strengthening the glass-ceramic provided by any of the embodiments in the aforementioned embodiments, and the surface compressive stress CS of the chemically strengthened glass-ceramic is greater than or equal to 200MPa, the depth of the compressive stress layer DOL_0 is greater than or equal to 90μm, and the four-point bending strength 4PB is greater than or equal to 950MPa. It is worth mentioning that the specific test method of the four-point bending strength test of the present application is: upper span 20mm / lower span 40mm, descending speed 10mm / min, until the glass breaks, and the maximum bending strength value when broken is recorded.
[0047] Accordingly, an embodiment of the present application further provides a method for preparing a glass-ceramic product, which specifically includes:
[0048] Step A, preparing raw materials in corresponding formula proportions according to the components of glass-ceramics;
[0049] Step B, after the raw materials are evenly mixed, they are melted at a preset melting temperature for a preset time to obtain a precursor glass;
[0050] Step C, heat-treating the precursor glass at 500-530° C. for 0.5-5 h, then at 550-580° C. for 1-4 h, then at 680-750° C. for 0.5-1.5 h, and finally cooling to room temperature to obtain microcrystalline glass.
[0051] In practical applications, glass raw materials are first prepared according to the components and contents of the microcrystalline glass provided in the aforementioned embodiments, and the glass raw materials are evenly mixed and melted at 1580°C, and then the precursor glass is obtained after clarification, homogenization, molding, and annealing. Then, the precursor glass is crystallized by a three-stage heat treatment method. The first step of the heat treatment is a microphase separation treatment, the second step of the heat treatment is a nucleation treatment, and the third step of the heat treatment is a crystallization treatment. Then, it is cooled to room temperature to obtain microcrystalline glass that meets the expected crystallinity, grain size and crystal phase ratio.
[0052] It should be noted that the crystallization process of glass includes two necessary steps: nucleation and crystal growth. The number and uniformity of the crystal nuclei formed during the nucleation process have a great influence on the crystal phase and crystal size. Generally speaking, the more and more uniform the crystal nuclei are, the smaller the crystal particles can be obtained, and the microcrystalline glass can have better transmittance and strength.
[0053] In this embodiment, the purpose of implementing the first step of the heat treatment in the three-stage heat treatment process is to first form microphase separation in the glass, and to form a sufficient number of phase separation regions in the glass within this stage to provide conditions for the formation of a sufficient number of crystal nuclei. Next, the purpose of implementing the second step of the heat treatment is to nucleate in the separated droplet phase. With the foundation of the droplet phase formed by the first step of the heat treatment, more crystal nuclei can be controlled to achieve the purpose of grain refinement. Finally, the third step of the heat treatment is to complete the growth of the crystal. It is worth mentioning that based on the design of the three-stage heat treatment process in this embodiment, the nucleation process can be made more controllable by controlling the phase separation energy, thereby obtaining a microcrystalline glass that meets the expected crystallinity, grain size and crystal phase ratio.
[0054] Specifically, the crystalline phases of the microcrystalline glass include petalite, lithium disilicate and lithium silicate, and the degree of crystallinity is less than or equal to 90%; the ratio of the content of petalite to the total crystal content is 45-60%, the ratio of the content of lithium disilicate to the total crystal content is 30-45%, the ratio of the content of lithium silicate to the total crystal content is less than or equal to 13%, and the ratio of the combined content of petalite and lithium disilicate to the total crystal content is greater than or equal to 75%.
[0055] It is worth mentioning that, based on the optimized glass formula system and oxide content provided in the embodiments of the present application, combined with the setting of the crystallization treatment process, a higher degree of crystallinity can be achieved directly through a single crystallization treatment process, without the need for a composite crystallization treatment method of pre-crystallization and then heat treatment to achieve the expected degree of crystallinity, thereby simplifying the production process while meeting the expected optical properties and mechanical strength properties.
[0056] Preferably, the preparation method of the microcrystalline glass product also includes: after preheating the microcrystalline glass, placing it in a chemically strengthened salt bath for ion exchange treatment; taking out the microcrystalline glass that has undergone ion exchange treatment from the chemically strengthened salt bath and performing slow cooling and cleaning treatment to obtain chemically strengthened microcrystalline glass; wherein the surface compressive stress of the chemically strengthened microcrystalline glass is greater than or equal to 200MPa, the depth of the compressive stress layer is greater than or equal to 90μm, and the four-point bending strength is greater than or equal to 950MPa.
[0057] When chemically strengthening the glass-ceramics, the chemical strengthening salt bath includes 75% KNO3 and 25% NaNO3 by weight, and the temperature of the ion exchange treatment is 460°C and the duration is 400 to 500 minutes.
[0058] Chemical strengthening refers to placing the microcrystalline glass in a salt bath for ion exchange treatment, so that the microcrystalline glass forms a compressive stress layer and a tensile stress layer. The salt bath of this embodiment is a mixed salt bath. Compared with the traditional multiple strengthening, this embodiment can strengthen in a tempering furnace once to complete multiple ion exchange behaviors between the salt bath and the microcrystalline glass at the same time, thereby improving the chemical strengthening efficiency and reducing the amount of salt bath used. After chemical strengthening treatment, the chemically strengthened microcrystalline glass obtained has a deeper compressive stress layer depth and a higher surface compressive stress.
[0059] In an optional implementation manner of the present embodiment, the above-mentioned slow cooling cleaning treatment specifically includes: placing the microcrystalline glass that has completed the ion exchange treatment in an ultrasonic cleaning device, and passing through the citric acid tank, the first pure water tank, the neutral cleaning agent tank, the spray tank, the second pure water tank, and the slow pulling water tank of the ultrasonic cleaning device for slow cooling cleaning in sequence, and then passing through a drying tank for drying; wherein, the citric acid mass concentration of the citric acid tank is 4%, the pH value is 3-4, the temperature is room temperature, and the cleaning time is 30-180s; the pH value of the neutral cleaning agent tank is 8-10, the temperature is 50-60°C, and the cleaning time is 180s; the spray material of the spray tank is pure water, the water temperature is 50-60°C, and the cleaning time is 90s; there are multiple second pure water tanks (for example, four), the water temperature is 50-60°C, and the cleaning time is 180s; the water temperature of the slow pulling water tank is 65-75°C, the cleaning time is 180s; the drying treatment time of the drying tank is 180s. It should be noted that the microcrystalline glass that has undergone ion exchange treatment and is taken out from the molten salt in the embodiment of the present application is first soaked in citric acid to achieve acid-base neutralization, thereby reducing the adhesion of abrasive powder on the glass surface and making it easier to clean in the subsequent stage. The final chemically strengthened microcrystalline glass has improved acid resistance compared to other microcrystalline materials.
[0060] Next, in order to illustrate the technical effect of the microcrystalline glass of this embodiment, the present application conducted tests on microcrystalline glasses of different components and contents to determine the characteristics of each microcrystalline glass. Examples 1 to 11 in Table 1 show the components, contents, test conditions and test results of the microcrystalline glasses of various different compositions of the present application. Comparative Examples 1 and 2 show the specific components, contents, test conditions and test results of several microcrystalline glasses provided in the prior art.
[0061] Table 1
[0062]
[0063]
[0064] According to the comparison of the test data of Examples 1 to 11 and Comparative Examples 1 to 2 in Table 1 above, it can be seen that, on the one hand, the mechanical strength properties (Vickers hardness, elastic modulus, shear modulus, Poisson's ratio, fracture toughness) of the microcrystalline glass obtained after crystallization in the examples of the present application are different from those of the comparative examples but are basically similar, which to a certain extent ensures that the mechanical strength properties of the microcrystalline glass are at a relatively excellent level; on the other hand, the microcrystalline glass obtained after crystallization in the examples of the present application has an average crystal particle size significantly smaller than that of the comparative examples, and a lower degree of crystallinity than that of the comparative examples, which makes the |B| value and haze of the microcrystalline glass in the examples of the present application significantly lower than those of the comparative examples, and the transmittance significantly higher than those of the comparative examples, so that it can be seen that the optical properties of the microcrystalline glass in this example have been significantly improved.
[0065] Furthermore, the present application also tests the performance of the glass-ceramics of various components and contents shown in the above-mentioned Examples 1 to 11 after chemical strengthening treatment. The specific test results are shown in Table 2:
[0066] Table 2
[0067]
[0068] Based on the test results in the above table, it can be seen that the surface compressive stress of the chemically strengthened microcrystalline glass provided in the embodiments of the present application can reach more than 225 MPa, the depth of the compressive stress layer can reach more than 115 μm, and the four-point bending strength can reach more than 965 MPa. It can be seen that the chemically strengthened microcrystalline glass provided in the embodiments of the present application has achieved relatively excellent mechanical properties.
[0069] Based on the above scheme of the present application, the crystal phases of the microcrystalline glass include petalite, lithium disilicate and lithium silicate, and the crystallinity is less than or equal to 90%; the ratio of the content of petalite to the total crystal content is 45-60%, the ratio of the content of lithium disilicate to the total crystal content is 30-45%, the ratio of the content of lithium silicate to the total crystal content is less than or equal to 13%, and the ratio of the total content of petalite and lithium disilicate to the total crystal content is greater than or equal to 75%. Through the implementation of the present application, the content and crystal size of different crystal phases are controlled in a specific ratio, which can ensure that the microcrystalline glass products have excellent optical properties while having good mechanical strength properties.
[0070] It is also worth mentioning that due to the above-mentioned performance advantages of the microcrystalline glass and chemically strengthened microcrystalline glass provided in the embodiments of the present application, they can be widely used in the production of protective cover plates of electronic devices, optical elements, photovoltaic devices or windows of household appliances.
[0071] Finally, it should be noted that in the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0072] The above is a description of the preparation method of the microcrystalline glass, chemically strengthened microcrystalline glass and microcrystalline glass products provided in the present application. For those skilled in the art, based on the ideas of the embodiments of the present application, equivalent substitutions made in the specific implementation methods and application scopes should all be included in the scope of the claims of the present application. In summary, the content of this specification should not be understood as a limitation on the scheme of the present application.
Claims
1. A glass-ceramic, characterized in that: The crystalline phases of the microcrystalline glass include petalite, lithium disilicate and lithium silicate, and the crystallinity is less than or equal to 90%; the ratio of the content of petalite to the total crystal content is 45-60%, the ratio of the content of lithium disilicate to the total crystal content is 30-45%, the ratio of the content of lithium silicate to the total crystal content is less than or equal to 13%, and the ratio of the total content of petalite and lithium disilicate to the total crystal content is greater than or equal to 75%.
2. The glass-ceramic according to claim 1, characterized in that: The crystal phase of the microcrystalline glass also includes at least one of lithium phosphate and β-spodumene.
3. The glass-ceramic according to claim 1, characterized in that: The crystallinity of the microcrystalline glass is 80-85%.
4. The glass-ceramic according to claim 1, characterized in that: The content of petalite accounts for 50-55% of the total crystal content, and / or the content of lithium disilicate accounts for 35-40% of the total crystal content, and / or the content of lithium silicate accounts for 8-13% of the total crystal content.
5. The glass-ceramic according to claim 1, characterized in that: Its components, measured by weight percentage, include: SiO2: 70-75%, B2O3: 0.35-1.2%, Al2O3: 7.5-9.5%, Na2O: 0.5-1.5%, Li2O: 9.5-12%, P2O5: 1.8-2.6%, and ZrO2: 3.5-5.5%.
6. The glass-ceramic according to claim 5, characterized in that: Its components, measured by weight percentage, include: SiO2: 70-72%, B2O3: 0.5-1.2%, Al2O3: 8-9.5%, Na2O: 1-1.5%, Li2O: 10.5-12%, P2O5: 1.8-2.6%, and ZrO2: 3.5-5.5%.
7. The glass-ceramic according to claim 5, characterized in that: Its components, in terms of weight percentage, meet the following conditions: Li2O / (SiO2+Al2O3): 0.1-0.
2.
8. The glass-ceramic according to claim 5, characterized in that: The components thereof, in terms of weight percentage, further include: K2O: 0-1%, Y2O3: 0-0.5%, and clarifier: 0-0.4%.
9. The glass-ceramic according to claim 8, characterized in that: The components thereof, in terms of weight percentage, further include: K2O: 0.5-1%, Y2O3: 0.2-0.5%, and clarifier: 0.2-0.4%.
10. The glass-ceramic according to any one of claims 1 to 9, characterized in that: Meet at least one of the following indicators: Vickers hardness greater than or equal to 730kgf / mm 2 , the average crystal particle size is less than or equal to 30nm, the average transmittance of visible light with a wavelength of 380-780nm is greater than or equal to 85% when the thickness is 0.6mm, the |B| value is less than or equal to 0.6 when the thickness is 0.6mm, and the haze is less than or equal to 0.15 when the thickness is 0.6mm.
11. A chemically strengthened glass-ceramic, characterized in that: The chemically strengthened glass-ceramics is obtained by subjecting the glass-ceramics as described in any one of claims 1 to 10 to chemical strengthening treatment, wherein the surface compressive stress of the chemically strengthened glass-ceramics is greater than or equal to 200 MPa, the depth of the compressive stress layer is greater than or equal to 90 μm, and the four-point bending strength is greater than or equal to 950 MPa.
12. A method for preparing a glass-ceramic product, characterized in that: include: Prepare raw materials with corresponding formula proportions according to the components of glass-ceramics; After the raw materials are uniformly mixed, they are melted at a preset melting temperature for a preset time to obtain a precursor glass; The precursor glass is first heat-treated at 500-530° C. for 0.5-5 h, then heat-treated at 550-580° C. for 1-4 h, then heat-treated at 680-750° C. for 0.5-1.5 h, and finally cooled to room temperature to obtain the microcrystalline glass; Among them, the crystalline phases of the microcrystalline glass include petalite, lithium disilicate and lithium silicate, and the crystallinity is less than or equal to 90%; the ratio of the content of petalite to the total crystal content is 45-60%, the ratio of the content of lithium disilicate to the total crystal content is 30-45%, the ratio of the content of lithium silicate to the total crystal content is less than or equal to 13%, and the ratio of the total content of petalite and lithium disilicate to the total crystal content is greater than or equal to 75%.
13. The preparation method according to claim 12, characterized in that: The components of the microcrystalline glass, measured in weight percentage, include: SiO2: 70-75%, B2O3: 0.35-1.2%, Al2O3: 7.5-9.5%, Na2O: 0.5-1.5%, Li2O: 9.5-12%, P2O5: 1.8-2.6%, and ZrO2: 3.5-5.5%.
14. The preparation method according to claim 12 or 13, characterized in that: Also includes: After preheating the glass-ceramics, the glass-ceramics are placed in a chemically strengthened salt bath for ion exchange treatment; The microcrystalline glass that has undergone ion exchange treatment is taken out from the chemically strengthened salt bath and subjected to slow cooling and cleaning treatment to obtain a chemically strengthened microcrystalline glass; wherein the surface compressive stress of the chemically strengthened microcrystalline glass is greater than or equal to 200MPa, the depth of the compressive stress layer is greater than or equal to 90μm, and the four-point bending strength is greater than or equal to 950MPa.
15. The preparation method according to claim 14, characterized in that: The chemical strengthening salt bath includes 75% KNO3 and 25% NaNO3 by weight percentage, and the temperature of the ion exchange treatment is 460°C and the duration is 400-500 minutes.
Citation Information
Cited By
Glass ceramic with high reliability, chemically strengthened glass ceramic and glass preparation method
CN120647159A
Precursor glass, glass ceramic, chemically strengthened glass ceramic and glass preparation method
CN120794348A
